An Investigation of Diatom Communities in Choctawhatchee Bay in Response to the BP Oil Spill - Malik, Heera Ilahi (My University, 2012)
The primary objective of this research was to characterize the structure of the diatom community in Choctawhatchee Bay in response to the BP oil spill. Three types of samples, net plankton, sediment, and whole water, were collected on a bimonthly basis for six months. Diatoms in the samples were identified at the species level whenever possible by both light microscopy (LM) and scanning electron microscopy (SEM). A total of 87 genera and 437 species were recorded; this represents approximately 40% of species previously recorded in the Gulf of Mexico. Net plankton samples were compared with historical data to determine if a significant shift in the community structure had occurred; the absence of similar data did not permit a comparison of sediment communities. Current and historical plankton associations showed only a 28% similarity. This low similarity could be result of natural variation in the composition of the phytoplankton, differences in sampling techniques used, differences in the application of taxonomic principles, or changes brought about by the BP oil spill. At this point we cannot distinguish which of these is the most important factor. Moreover, the number of abnormal valves observed, much less than 0.1% of the total number of valves, argues against a major impact of the BP oil spill on the diatom community.
Summer 2012 Biology thesis of Heera I. Malik
Keywords: biology; Choctawhatchee Bay; Florida; BP Oil Spill; Oil; British Petroleum; diatom; plankton; species; Gulf of Mexico